Improvements in domestic water services in Kelantan: are people willing to pay? - Kamaludin, Mahirah; Abdul Rahim, Khalid; Radam, Alias; Yacob, Mohd Rusli (Penerbit Universiti Malaysia Terengganu, 2013)
This study evaluated the willingness to pay by the people in Kelantan for improved domestic water services. Unsatisfactory services by the Kelantan water company are a long-standing issue in the state. Excessive water consumption, frequent interruptions, rapid social and economic growths are putting higher demands for quality of services and the water company is unable to cope with the growing number of populations. This study employed Choice Experiment (CE) method to examine other possible preferences in domestic water services. This method highlighted four attributes such as water quality (QUAL), water interruption (INT), non revenue water (NRW) and water prices (WP) in its services. Respondents were required to trade off their income for positive changes in the services. Basic and interactions in Conditional Logit (CL) models were estimated to account for heterogeneity in the selected choices of the consumers from options provided in water service attributes. A survey has been carried out with 552 respondents based in every district (stratum) in the state. It is interesting to note that of the four attributes considered in this study, reducing the frequency of water interruption becomes a priority in the services for the population.